Association Between Metabolic Syndrome and Decline in Cognitive Function: A Cross-Sectional Study - Hissa N Alsuwaidi (21407003) (2023)
Aim We investigated whether metabolic syndrome (MetS) is associated with a decline in cognitive function in a cohort of middle-aged and elderly individuals without known cognitive dysfunction diseases in Qatar. Methods We conducted a cross-sectional study on randomly selected participants aged 40– 80 years from the Qatar Biobank, with data on cognitive tests and MetS components. Participants with a history of dementia, stroke, or mental disorders were excluded. MetS was diagnosed using the NCEP-ATP III criteria and cognitive performance was assessed using the Cambridge Neuropsychological Test Automated Battery (CANTAB). Two cognitive function domains were assessed. These are speed of reaction, measured using the Reaction Time (RT), and short-term visual memory, measured using the Paired Associate Learning (PAL) test. Multivariable logistic regression models were used to determine associations between MetS and poor speed of reaction and poor memory performance. Results The mean age of the participants included was 49.8 years (SD 6.7). Of these, 51.9% were females and 88.0% were of Qatari nationality. Most of the 1000 participants had MetS (n=302) or 1– 2 MetS components (n=523), whereas only 170 had no MetS components. There was a strong association between MetS and poor memory performance (OR 1.76, 95% CI 1.04– 2.96, P=0.034), but a weaker association with poor speed of reaction (OR 1.5, 95% CI 0.89– 2.50, P=0.125). Conclusion In middle-aged and elderly individuals, MetS was strongly associated with diminished short-term visual memory, psychomotor coordination and motor speed. Other Information Published in: Diabetes, Metabolic Syndrome and Obesity License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/dmso.s393282